Biogeochemistry of holocene peatlands in the baraba forest-steppe (southern West Siberia). (January 2021) - Leonova, G.А.; Maltsev, А.Е.; Preis, Yu.I.; Miroshnichenko, L.V.
Abstract: Postdepositional diagenetic processes and behavior of biogenic and other elements in Holocene peatlands have been studied in Ubinskoe and Sherstobitovo bogs of the Baraba forest-steppe zone. Peat contains relatively high concentrations of Fe, Mn, Pb, Hg, Sb, Cd, Cu, and Zn in the upper part of the two sections and S, N, Ca, and Sr in the middle. Microbially mediated processes in peat affect the behavior of pH and Eh and cycles of biogenic elements. Depth-dependent distribution patterns of microorganisms in the two bogs record active cycles of carbon and nitrogen but limited sulfur exchange. Bog waters have Ca-group bicarbonate major-ion chemistry and high concentrations of Al, Fe, Cu, and Zn, due to low pH. High contents of NH4 +, NO3 −, and Corg and chemical oxygen demand (COD) in the bog waters are implicit indicators of rapid biochemical decomposition and oxidation of organic matter. The low pH of the water and an oxic environment in peat were favorable for the formation of goethite and hydrogoethite in upper peat layers. The formation of hematite and andhydride may be related with past wild fires. Early diagenetic processes lead to precipitation of authigenic minerals, especially, pyrite or less often siderite, calcite, and kaolinite. Reduced conditions maintained the formation of metallic Ni and intermetallic Ni–Cr nanometer particles, as well as precipitation of amorphous silica upon dissolution of aluminosilicate minerals in upper peat intervals. Highlights (for review): Postdepositional diagenetic processes and behavior of biogenic and other elements in Holocene peatlands have been studied.